"ECOFEMINISM IN WORKS OF ALFRED TENNYSON" - Nirupama Prakash (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
Alfred, Lord Tennyson’s poem, "The Lady of Shallot," includes the mysterious account, mostly for women who have been subject to patriarchy, which may be regarded as most important for society. The poem is an elusive transmission of Victorian Britain’s unbalanced gender ideology, employing a metaphor that brings with it social and cultural circumstances. In addition, the images of both genders are strongly emphasised as either public and private, or dominant and submissive, respectively. Feminism developed when women gathered behind closed doors to indulge in needlework. Jobs like governor, nurse and mother-in-law have the right to women since these professions are what they usually perform in their private field. But, since they are really important to society, they were ultimately recognised for their vocations. The Lady of Shalott is also only recognised from Camelot’s public realm if, despite difficulty and even grief, she runs from isolating herself.